Invasive surgery reduces infarct size and preserves cardiac function in a porcine model of myocardial infarction. Issue 11 (18th August 2015) - van Hout, Gerardus P.J.; Teuben, Michel P.J.; Heeres, Marjolein; de Maat, Steven; de Jong, Renate; Maas, Coen; Kouwenberg, Lisanne H.J.A.; Koenderman, Leo; van Solinge, Wouter W.; de Jager, Saskia C.A.; Pasterkamp, Gerard; Hoefer, Imo E.
Abstract: Reperfusion injury following myocardial infarction (MI) increases infarct size (IS) and deteriorates cardiac function. Cardioprotective strategies in large animal MI models often failed in clinical trials, suggesting translational failure. Experimentally, MI is induced artificially and the effect of the experimental procedures may influence outcome and thus clinical applicability. The aim of this study was to investigate if invasive surgery, as in the common open chest MI model affects IS and cardiac function. Twenty female landrace pigs were subjected to MI by transluminal balloon occlusion. In 10 of 20 pigs, balloon occlusion was preceded by invasive surgery (medial sternotomy). After 72 hrs, pigs were subjected to echocardiography and Evans blue/triphenyl tetrazoliumchloride double staining to determine IS and area at risk. Quantification of IS showed a significant IS reduction in the open chest group compared to the closed chest group (IS versus area at risk: 50.9 ± 5.4% versus 69.9 ± 3.4%, P = 0.007). End systolic LV volume and LV ejection fraction measured by echocardiography at follow‐up differed significantly between both groups (51 ± 5 ml versus 65 ± 3 ml, P = 0.033; 47.5 ± 2.6% versus 38.8 ± 1.2%, P = 0.005). The inflammatory response in the damaged myocardium did not differ between groups. This study indicates that invasive surgery reduces IS and preserves cardiac function in a porcine MI model. Future studies need to elucidate the effect of infarct induction technique on the efficacy of pharmacological therapies in large animal cardioprotection studies.